Development of Self Stigma Assessment Tool for People Living With HIV/AIDS (PLWHA) - Martiningsih, Wiwin; Suprajitno; Mulyadi, Arif; Winarni, Sri; Retnaningtyas, Ekowati (National Journal of Community Medicine, 2024)
Introduction: Stigma does not only come from people who give negative judgment to HIV/AIDS patients but also from patients themselves. This study explored the experiences of the self-stigma of people living with HIV/AIDS (PLWHA) and developed the self-stigma tool for PLWHA. Methodology: We conducted a mixed-method study using an exploratory-sequential design in the East Java community, Indonesia. In the first phase, we identified 12 PLWHA through snowball sampling, and in the second phase, 133 PLWHA participated. We collected data through indepth interviews. Subsequently, the insights gained from these interviews were utilized to develop a tool for assessing self-stigma among PLWHA, known as the MARSUDI self-stigma tool. Results: The first phase of the study revealed three main themes: 1) the feeling of self-stigma, 2) the coping mechanism, and 3) suggestions to combat the stigma. Moving on to the second phase, the MARSUDI self-stigma tool for PLWHA was developed. This tool comprises 26 items, achieving a s-cvi score exceeding 0.80. Following factorial analysis, 20 items remained with a loading factor surpassing 0.6, and contributing to 66.24% of the total variance. These items were categorized into three factors: Factor 1 (self-perception) includes 7 items, Factor 2 (self-labelling) consists of 11 items, and Factor 3 (self-discrimination) comprises 2 items. Conclusion: The results of this study revealed that the MARSUDI self-stigma of PLWHA is valid, reliable, and acceptable.